Reality Perception of Gamers & Game Designers: Creation of Possible Worlds in Video-games - Luckinger, Yunus (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This thesis explores and studies the creation of possible world for different genre of video-games and analyzes the distinctive features which are relevant to the creation of possible world for video-games. For the purpose of this research, qualitative research method selected in order to have better understanding of two group of the gamers (the people who play minimum eight hours daily) and video-game designers perception. The differences of their perception regarding how they perceive signs and associate it with video-game genres is the main concern of this research. Thus, ten video-game designer based on snowball sampling technique were selected as well as ten gamers based on purposive sampling technique were selected from an application for voice communication called Discord which is frequently used by gamers to communicate online. Two set of open ended questions prepared for each groups of interviewee, however, some of the questions were the same. Nine video-games form each genre (action, adventure, action-adventure, role-playing, strategy, simulation, sport, puzzle, idle) were randomly selected for this study. The results shows that there is a small difference in their perceptions based on the possible world of the games and gamers see the possible world of video-games more close to the reality than the video-game designers. According to the findings each genre of video-games has some perceivable marked signs that separated the genre of video-games which was similar between the two groups of interviewees. The possible world of each video-game is the result of selection and combination of time, location, behavior of characters, characters, objects and game style, which makes the possible world of the game far or close to the real world. Keywords: video-game; possible world; selection and combination

ÖZ:Bu tez, farklı video oyun türleri için olası bir dünyanın yaratılmasını incelemekte ve video oyunları için yapılan olası bir dünyanın yaratılması ile ilgili ayırt edici özellikleri analiz etmektedir. Bu araştırmanın amacı doğrultusunda, oyuncular (günde en az 8 saat oyun oynayanlar) ve video oyunu tasarımcılarının algısını daha iyi anlamak için nitel araştırma yöntemi seçilmiştir. İşaretleri nasıl algıladıkları ve video oyunu türleri ile nasıl ilişkilendirdikleri konusundaki algı farklılıkları bu araştırmanın temel kaygısıdır. Bu tezde, kartopu örnekleme tekniğine dayanan on oyun tasarımcısı ve Discord adı verilen sesli iletişim uygulamasından, yargılayıcı örnekleme tekniğine dayanan on oyuncu seçilmiştir. Her bir görüşmeci grubu için iki açık uçlu soru seti hazırlanmıştır. Ancak bazı sorular iki grup için de aynı olmaktadır. Her türden (aksiyon, macera, aksiyon-macera, rol yapma, strateji, simülasyon, spor, bulmaca, boş) dokuz video oyunu, bu çalışma için rastgele seçilmiştir. Sonuç olarak, oyunların olası dünyasına göre, iki grubun algılarında küçük bir fark olduğu belirlenmiştir. Oyuncular, oyun tasarımcılarına göre, oyunların olası dünyalarını gerçeğe daha yakın olarak algılamaktadırlar. Aynı zamanda oyun türlerinde, her tür için, belirgin işaretler olduğu ve bu işaretlerin iki grubun arasında benzer olduğu görülmektedir. Her video oyununun; olası dünyası, zaman, konum, karakterlerin davranışı, karakterler, nesneler ve oyun stili seçiminin ve kombinasyonunun sonucudur ve bu da oyunun olası dünyasını gerçek dünyaya yakın ya da uzak kılar. Anahtar Kelimeler: video oyunu; olası dünya; seçim ve kombinasyon
Doctor of Philosophy in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2019. Supervisor: Asst. Prof. Dr. Aysu Arsoy.
Keywords: Video games-Psychological aspects; Computer games-Psychological aspects; Video games-Social aspects; Technology and the arts-Computer games-Design--Human-Computer interaction; video-game; possible world; selection and combination